The Slave's Narrative. - Davis, Charles T. (Charles Twitchell), 1918-1981; Gates, Henry Louis, Jr (Oxford University Press, 1991)
This textbook has been designed to confront a central issue in the study of 19th-century Afro-American literature - the question of how to analyse and evaluate the autobiographical tradition of ex-slaves.